Development Of Motion Graphic Video Media In Promoting Embung Puri Idaman Tourism In Purwosari Village - Riska, Sherly Nur; Husin, Azizah; Waty, Evy Ratna Kartika (UNDIKMA, 2024)
This study aims to analyze and develop video media that is valid and practical as a medium for promoting embung puri idaman tourism in purwosari village, East Oku district. This research is a development research using the borg and gall research model. The practicality and validity of the media were assessed by three expert validators, namely language expert validation, media expert validation, and material expert validation. The implementation of promotional video media was carried out in two stages, namely one to one trials and small group trials. The result of this study is a promotional video media tour that has an average level of validity on experts 93.5% with a very practical category. While the feasibility score at the one to one stage is 97.5% with a very feasible category, and at the small group stage is 86.42% with practical and valid categories. Based on the results of the above research, therefore, the tourism promotion video media developed attracts the attention of potential tourists, which is stated to foster interest in visiting Embung Puri Idaman so that it can be used.